Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/dme.13590
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the economic value of maintained improvements in Type 1 diabetes management, in terms of HbA1c, weight and hypoglycaemic event incidence

Abstract: AimsInsulin therapy is indicated for people with Type 1 diabetes mellitus; however, treatment‐related weight gain and hypoglycaemia represent barriers to optimal glycaemic management. This study assessed the health economic value of maintained reductions in HbA1c, BMI and hypoglycaemia incidence among the UK Type 1 diabetes population.MethodsThe Cardiff Type 1 Diabetes Model was used to estimate lifetime costs, life‐years and quality‐adjusted life‐years (QALYs) for individuals with Type 1 diabetes at different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Microvascular complications such as retinopathy, neuropathy and nephropathy, and macrovascular complications such as cardiovascular disease and stroke, make up approximately 70% of the overall National Health Service (NHS) budget for T1D in the UK 4 . Improving glycaemia, targeting individuals at the highest risk and reducing exposure to hypoglycaemia would be the most beneficial approaches to reducing care costs for people with T1D 5 …”
Section: Introductionmentioning
confidence: 99%
“…Microvascular complications such as retinopathy, neuropathy and nephropathy, and macrovascular complications such as cardiovascular disease and stroke, make up approximately 70% of the overall National Health Service (NHS) budget for T1D in the UK 4 . Improving glycaemia, targeting individuals at the highest risk and reducing exposure to hypoglycaemia would be the most beneficial approaches to reducing care costs for people with T1D 5 …”
Section: Introductionmentioning
confidence: 99%
“…Our further analysis of healthcare service utilization found that patients with a history of DM-related complications and an increasing number of comorbidities were associated with greater hospitalization admission rates during the event year. Correspondingly, the increase in direct medical costs was associated with poor glycaemic control, 30 treatment intensification, 31 incidence of DM-related complications 23,32 and all-cause mortality. 22 Annual direct medical costs grew by 95.3% from 2481 US$ during the 2 years preceding the SH event to 4846 US$ during the year immediately preceding the SH.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of analysing the health economic and social impacts of the use of technology in diabetes management and prevention was highlighted, particularly in light of the need to demonstrate clear benefit to change NHS policy. Aspects of diabetes technology in need of this type of assessment include the potential for glucose monitoring technology or closed loop systems to prevent poor health outcomes with a major health economic cost through reducing HbA1c 40,41 and the reduction in interrupted sleep for parents of young children with diabetes which glucose monitoring technology can provide. 42…”
Section: Health Economics and Social Impactmentioning
confidence: 99%